2010
DOI: 10.1111/j.1365-3164.2009.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hand-held evaporimeter (VapoMeter®) for the measurement of transepidermal water loss in healthy dogs

Abstract: In humans, transepidermal water loss (TEWL) is measured by noninvasive techniques using either open- or closed-chamber instruments. The aim of this study was to investigate the use of a hand-held, closed chamber device (Vapometer) to measure TEWL in canine skin. Repeated measurements obtained from multiple body sites in one short and one long-coated dog had mean coefficients of variation ranging from 20% to 33%. In the short-coated dog, TEWL ranged from a mean of 5.8 g/m(2)/h on the ventral abdomen to 24.4 g/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 45 publications
(113 reference statements)
3
55
3
2
Order By: Relevance
“…Lau‐Gillard et al. 10 showed that TEWL measurements varied from site to site, day to day and dog to dog. Using an experimental canine model in which confounding factors are controlled can limit these undesirable variations.…”
Section: Discussionmentioning
confidence: 99%
“…Lau‐Gillard et al. 10 showed that TEWL measurements varied from site to site, day to day and dog to dog. Using an experimental canine model in which confounding factors are controlled can limit these undesirable variations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much research involving the assessment of skin biophysical parameters has been published (Dirschka et al 2005, Fluhr et al 2006, Hightower et al 2008, Oh and Oh 2009, Cornegliani et al 2011. Much attention has been given to the assessment of these parameters in dogs (Beco et al 2000, Matousek et al 2002, Watson et al 2002, Young et al 2002, Hester et al 2004, Yoshihara et al 2004, Oh and Oh 2009, Shimada et al 2009, Hightower et al 2010, Lau-Gillard et al 2010, Ohmori et al 2010, Cornegliani et al 2011, Marshala 2012. Some papers tackled the issue of measuring the parameters in cats (Bourdeau et al 2004, Vidal et al 2009, Szczepanik et al 2011) and horses (Meyer andNeurand 1991, Szczepanik et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the same precautions were taken to minimize the factors that could interfere with the measurement of the TEWL such as allowing acclimation time, a controlled environment with consistent temperature and humidity, and a close chamber device which should be the least affected by ambient factors. Although the closed chamber devices are considered more reliable than the open chamber, limitations still exist and great variability can be found, and this makes it sometimes difficult to detect significant differences [34]. …”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with a compilation of studies in which no significant correlations were found between the TEWL assessment and the CADESI evaluation [35]. TEWL values have been reported to increase in proportion to the level of artificial damage of the skin [36]; however, for use in clinical studies, the significant site-to-site, day-to-day, and dog-to-dog variations make it very difficult for changes induced by disease, drugs, dietary supplements, or topical agents to be reliably detected as previously described by other investigators [34]. In order to reduce these variations, all dogs enrolled in our study were not affected by other disease except the mild AD, stayed on the same diet throughout the study, and were off drugs except flea control.…”
Section: Discussionmentioning
confidence: 99%